Recommendations for evaluating the performance of background subtraction algorithms for surveillance systems - Sanches, Silvio Ricardo Rodrigues; Sementille, Antonio Carlos [UNESP]; Aguilar, Ivan Abdo; Freire, Valdinei (Springer, 2020)
Background subtraction is a prerequisite for a wide range of applications, including video surveillance systems. A significant number of algorithms are often developed and published in different publication mediums in the area, such as workshops, symposiums, conferences, and journals. An important task in presenting a new background subtraction algorithms is to clearly show that its performance outperforms the performance of the state-of-the-art algorithms. In this paper, we present recommendations on how to evaluate the performance of background subtraction algorithms for surveillance systems. We identified, through a systematic mapping, the key steps and components of this evaluation process - procedures, methods, and tools - most used by the authors in each of these steps. Considering this statistical analysis, we perform a theoretical analysis of the most used key components to identify their pros and cons. Then, we define a set of recommendations that aim to standardize and clarify the performance evaluation process of a new background subtraction algorithm.
Keywords: Background subtraction; Performance assessment; Recommendations; Surveillance systems